2018
DOI: 10.7567/jjap.57.090303
|View full text |Cite
|
Sign up to set email alerts
|

Electric transport properties for three-dimensional angular-interconnects of Au wires crossing facet edges of atomically-flat Si{111} surfaces

Abstract: The creation of atomically-ordered Si{111}7 × 7 facet structures on a Si(110) substrate is realized for the first time. Au was deposited on atomically-flat {111} facet surfaces. The resistance of Au wires crossing over three-dimensional (3D) facet edges with an angular shape is intrinsically sensitive to the edge alignments in electric path: the resistance in crossing the facet edges was 3–10 times larger than that along the facet edges. We suggest the enlargement of the resistance originated from conduction e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Ewald sphere in 3D RSM, for 3D crystal. 3D fabricated materials, the authors have demonstrated that not only substrate surfaces but also surfaces inclined from or perpendicular to a substrate plane exhibit atomically ordered structures where surface spots elongated along directions inclined from or perpendicular to the substrate normal direction appear in RHEED patterns ( Figure 5(b)) [6,7,9]. We emphasize that a simple surface property of 3D fabricated materials, that is, a surface direction, can be confirmed by the elongation of surface spots.…”
Section: Schematic Of Relationship Between Diffraction Spots and Recimentioning
confidence: 63%
See 4 more Smart Citations
“…Ewald sphere in 3D RSM, for 3D crystal. 3D fabricated materials, the authors have demonstrated that not only substrate surfaces but also surfaces inclined from or perpendicular to a substrate plane exhibit atomically ordered structures where surface spots elongated along directions inclined from or perpendicular to the substrate normal direction appear in RHEED patterns ( Figure 5(b)) [6,7,9]. We emphasize that a simple surface property of 3D fabricated materials, that is, a surface direction, can be confirmed by the elongation of surface spots.…”
Section: Schematic Of Relationship Between Diffraction Spots and Recimentioning
confidence: 63%
“…The process parameters were an ICP source power of 300 W, a bias power of 10 W, and a working pressure of 4 Pa. Mixture gases of 10 sccm SF 6 , 5 sccm O 2 , and 200 sccm Ar were used in the etching cycle, and 40 sccm C 4 F 8 , 5 sccm O 2 , and 200 sccm Ar were used in the passivation process [6][7][8][9]. Depending on dry RIE conditions, various curved structures from trapezoid to triangle shapes were obtained.…”
Section: Sample Fabrication With Combination Of Dry and Wet Etching Pmentioning
confidence: 99%
See 3 more Smart Citations